Hubungan Kadar Natrium Serum dengan Outcome Klinis pada Pasien Cedera Kepala Berat di RSUD Abdul Wahab Sjahranie Samarinda - Achmad Rivaldi; Arie Ibrahim; Loly Rotua Dharmanita Siagian (Jurnal Ilmiah Manuntung, 2020)
Recently, Traumatic Brain Injury (TBI) has high mortality in the world. In severe TBI, secondary brain injury can occur. ElectrSolyte disorders are the most common in secondary brain insult especially sodium disorders. It remains unclear whether hyponatremia or hypernatremia can cause worse clinical outcome in TBI patients. This study aimed to determine association between serum sodium level with clinical outcome in severe TBI patients at RSUD Abdul Wahab Sjahranie Samarinda. A cross sectional analytical study by taking samples to the patients with diagnosed severe TBI (GCS ≤ 8) which were hospitalized at RSUD Abdul Wahab Sjahranie Samarinda in the period of January-December 2018 that complied inclusion and exclusion criteria. Research variables are sodium serum level and clinical outcome that was assessed by structured interviews for Glasgow Outcome Scale (GOS). The relationship between variables was done using the Fisher's Exact test. A total of 41 severe TBI patients were administered. The characteristics of the sample were the most patients in 20s-40s (46.3%), patients were dominated by male (82.9%) and the most common CT scan characteristic were epidural hematoma (29.3%). The most of patients showed normonatremia in 25 patients (61%), 9 patients (22%) had hypernatremia and 7 patients (17.1%) had hyponatremia. The most clinical outcome on severe TBI patients were worse outcome with 70.7% while good outcome with 29.3%. Statistical result showed there’s no association between serum sodium level (hyponatremia and hypernatremia) with clinical outcome in severe TBI patients with p values, 1.000 and 0.225, respectively. There’s no association between serum sodium level with clinical outcome in severe TBI patients.